Visual Perception of Students with Mild Intellectual Disabilty - Monika Karolina Węglarz-Masłowska (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: Visual perception is an important cognitive ability, which influences other skills, including the mastery of school techniques by students with mild intellectual disabilities. An important goal of supporting of childhood education is to develop visual perception in all its aspects. Developing aspects such as hand-eye coordination, perception of figures and background, perception stability, spatial position and perception of spatial relationships has a positive effect on the math skills and writing and reading of early schoolchildren. Research Aim: The aim of the research was to learn about the functioning of students with mild intellectual disability in terms of 5 aspects of visual perception: visual and motor coordination, perception of the figure and background, perception of the constancy of shape, figure position and spatial relations, and to develop practical implications for developing this function. Method: The research used the method of diagnostic survey. The observation technique and the tool of M. Frostig and D. Horne "Visual Perception Test" were used to collect the data. Results: The level of functioning of the examined students with mild intellectual disability in terms of visual perception is below the norm. In all the subjects, a decrease in the level of visual perception was found in 3 of the examined areas; perception of the figure and background, shape and position of the figure. In terms of eye-hand coordination and the perception of spatial relations, the dominant students are those with the tested feature below their age norm.           Conclusions: On the basis of the obtained results, guidelines for working with students were formulated in order to improve their functioning in the field of visual perception in all examined aspects.